Evaluation method of penetrating jamming effectiveness for cognitive communication protection - Zhiguo SUN; Shuo XIAO; Yijie WU; Shiming LI; Zhenduo WANG (Tongxin xuebao)
In order to support the implementation of “multidimensional orthogonal configured communication protection between communication modules as well as parameters and interference” in cognitive communication countermeasures scenarios, jamming effectiveness requires module level responsiveness.A penetrating jamming effectiveness evaluation method was proposed.Firstly, the core parameters of each signal processing module were selected as evaluation parameters.Secondly, analytic hierarchy process (AHP) and entropy weight method (EWM) were used to determine the weight of indicators.The coordination problem in AHP was solved through expert weight allocation, and the weight allocation problem in EWM was solved through non-uniform mapping.Finally, the subjective and objective weights were weighed through game theory, and the jamming effectiveness was judged by the technique for order preference by similarity to ideal solution (TOPSIS).By conducting evaluation experiments on the jamming performance of the Link16 data link, taking into account multiple aspects such as jamming types, number of jamming frequencies, jamming duration, and system types.Experiment results demonstrate that the penetration-based jamming performance evaluation method not only provides a more intuitive representation of the relationship between evaluation results and metric parameters, but also possesses excellent jamming discrimination capability.